Adjustment for the influence of age and heart rate on Doppler measurements of left ventricular filling. Issue 12 (December 1992) - Stewart, Ralph A H; Joshi, Jayshee; Alexander, Neal; Nihoyannopoulos, Petros; Oakley, Celia M
Abstract : Objective —To determine the normal range of pulsed Doppler measurements of left ventricular filling adjusted for age and heart rate. Design —Multiple regression was used to measure the effects of age and heart rate on pulsed Doppler indices of left ventricular filling in normal subjects. These regression equations were used to calculate a predicted normal value and 95% confidence interval (95% CI) for any subject from his age and heart rate. Participants —61 subjects with no evidence of cardiovascular disease, aged 20 to 90 years, with a resting heart rate of 47–89 beats/min. Results —The effect of a 10 year increase in age was peak atrial filling velocity +15% (95% CI 12·0% to 18·5%); peak early filling velocity −3·2% (−6·0% to 0%); isovolumic relaxation time +6·2% (3·9% to 8·4%); acceleration time −3·8% (−6·0% to −1·5%); deceleration time +7·9% (5·1% to 10·8%). The effect of a 10 beat/min increase in heart rate was: peak atrial filling velocity +5·5% (1·2% to 10·1%); peak early filling velocity −4·0% (−8·1% to 2·0%); isovolumic relaxation time −2·5% (−4·6% to 0·6%); acceleration time −3·1% (−6·4% to 0·4%); decleration time −1·8% (−4·0% to 3·8%). Conclusion —For any individual, comparison of the predicted normal measurement and 95% CI with the observed measurement allows an assessment of the effects of disease on left ventricular filling that is independent of age and heart rate.